A wastewater‐based assessment of the impact of a minimum unit price (MUP) on population alcohol consumption in the Northern Territory, Australia. (20th July 2021) - O'Brien, Jake W.; Tscharke, Benjamin J.; Bade, Richard; Chan, Gary; Gerber, Cobus; Mueller, Jochen F.; Thomas, Kevin V.; Hall, Wayne D.
Abstract: Aim: To test if there was a reduction in alcohol consumption in wastewater samples in the Northern Territory of Australia after the implementation of a minimum unit alcohol price policy (MUP) in October 2018. Design, setting, cases: Between August 2016 and February 2020, wastewater samples were collected across 66 sites in the Northern Territory and all other states and territories in Australia. Samples were collected every 2 months in capital cities and every 4 months in regional places during this period. Overall, 4917 samples were taken (2816 before MUP and 2101 after). Measurements: The number of standard drinks per 1000 people per day in the respective catchment areas was estimated based on the concentration of an alcohol‐specific metabolite, ethyl sulphate in the samples (using the excretion factor of ethyl sulphate, the flow of wastewater entering the wastewater treatment plants and the population of each wastewater catchment). Findings: Results from a linear mixed model showed that there was a large drop in alcohol consumption immediately after the MUP in Northern Territory [estimated drop = 1231, 99% confidence interval (CI) = 830, 1633; 38.75%]. There was no significant drop in all other states/territories except for Queensland, which showed a significant but much smaller drop (estimated drop: 310; 99% CI = 114, 550). One year after the MUP, the drop narrowed to 520 (99% CI = 189, 851) and was no longer statistically significant in February 2020 (15 months after MUP; estimated drop = 283, 99% CI = −114, 681). Conclusions: Per‐capita consumption of alcohol appears to have decreased substantially in the Northern Territory of Australia immediately after the implementation of a minimum unit price but consumption steadily recovered and almost returned to the pre‐MUP consumption level after 15 months.